2021
DOI: 10.3390/land10040387
|View full text |Cite
|
Sign up to set email alerts
|

Stand Structure, Biomass and Carbon Storage in Gmelina arborea Plantation at Agricultural Landscape in Foothills of Eastern Himalayas

Abstract: In the modern era, Gmelina arborea plantations are a hotspot of future research because of their high carbon sequestration potential. The present work was conducted during 2018 to 2020 on a young unmanaged Gmelina farm to understand the ecosystem’s carbon and its dynamics. The study area was categorized into three age classes: ≤ 5, 5–10, and 10–15 years. In a plantation, Gmelina trees (10%) were randomly selected while other trees (90%) were also taken into the consideration for ecosystem carbon. A stratified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 45 publications
8
33
0
Order By: Relevance
“…Basal area is a good predictor for biomass (Gebrewahid and Meressa, 2020) and is often used as a surrogate for biomass and carbon (Balderas Torres and Lovett, 2013). In the present study, basal area was strongly correlated with tree density and with vegetation (AGB + BGB) carbon in line with the findings of many others (Poorter et al, 2015;Salunkhe and Khare, 2016;Amara et al, 2019;Tamang et al, 2021) S1).…”
Section: Soil Carbon Poolssupporting
confidence: 89%
See 2 more Smart Citations
“…Basal area is a good predictor for biomass (Gebrewahid and Meressa, 2020) and is often used as a surrogate for biomass and carbon (Balderas Torres and Lovett, 2013). In the present study, basal area was strongly correlated with tree density and with vegetation (AGB + BGB) carbon in line with the findings of many others (Poorter et al, 2015;Salunkhe and Khare, 2016;Amara et al, 2019;Tamang et al, 2021) S1).…”
Section: Soil Carbon Poolssupporting
confidence: 89%
“…The aboveground biomass carbon storage in the present study was comparable with various studies reported by others in Northeast India, for example, 16.24-130.82 Mg C ha −1 in Assam (Borah et al, 2013), 60.09-121.43 Mg C ha −1 in forests of Manipur (Thokchom and Yadava, 2017), while being lower than the reported value of 460.5 Mg C ha −1 in an old-growth pine forest of Meghalaya (Baishya and Barik, 2011). The estimated total biomass and carbon pool of the Northeast India forest sites are within the range reported from other Indian forest systems (Ravindranath et al, 1997;Chhabra et al, 2002;Devi and Yadava, 2015;Wagner et al, 2015;Gandhi and Sundarpandian, 2017;Solomon et al, 2017;Gogoi et al, 2020;Tamang et al, 2021). Several factors such as the age of the forest stand (Kolh et al, 2017), tree density (Garcia-Vega et al, 2020), diversity, and basal area (Joshi and Dhyani, 2018) influence the biomass and total vegetation carbon.…”
Section: Aboveground Biomass Carbon Stocksupporting
confidence: 45%
See 1 more Smart Citation
“…With increasing stand age, plantations vary in vegetation composition and community structure, which may influence the ecosystem C pool [8] by shifting stand densities, litter quality and quantity, and soil nutrients [9]. Previous studies have reported a significant increase in biomass C with plantation age, but no drastic variation, increase, or decrease is found in the soil organic carbon (SOC) stocks [10][11][12]. The SOC density in topsoil continued to increase and accounted for 71.0%, 36.9%, 71.4%, and 76.8% of the C density in the plant-soil ecosystem across a 3-, 10-, 25-, and 35-year chronosequence in H. ammodendron plantations [12].…”
Section: Introductionmentioning
confidence: 99%
“…Fruit cultivation is considered a potential tool of good agricultural practices that might be reduced by the impact of climate change (Rana and Rana, 2003;Jhalegar et al, 2012). Hence, the combination of trees, usually in different systems, increases productivity, improves the nutrient cycle, and helps maintain the ecological balance because of the "biological carbon sequestration potential" (Ospina, 2017;Rana et al 2020;Kumar et al 2021;Rai et al, 2021;Sheikh et al, 2021;Tamang et al, 2021). Given the above-mentioned fact, this review article showed the complete effect of fruit crops on carbon sequestration, that is, the process by which carbon source is taken from the atmosphere and stored in another place.…”
Section: Introductionmentioning
confidence: 99%